PENGARUH TOTAL QUALITY MANAGEMENT TERHADAP KINERJA ORGANISASI DENGAN INOVASI SEBAGAI VARIABEL MEDIASI - Marini Marini; Hesti Setiorini; Rina Yuniarti (National Conference on Applied Business, Education, & Technology (NCABET), 2021)
SMEs are an important sector in driving the wheels of the Indonesian economy that need attention for a better Indonesian economic condition. Bengkulu City is a province consisting of 9 sub districts which is always increasing. The purpose of this study was to determine the effect of Total Quality Management (TQM) on organizational performance mediated by innovation. This study used primary data in the form of a questionnaire to test the existing hyphotheses and analyzed using the   Structural Equation Model (SEM). The sample in this study amounted to 203 SMEs in Bengkulu city. Data were analyzed using descriptive statistical analysis using WarpPLS version 6.0 software. The result showed that: (1). Total Quality Managemen has a significant positive effect on organizational performance. (2). Innovation does not mediate the effect of Total Quality Management on organizational performance